Management of Non-Tax State Revenue from the Utilization of State Property - Allagan, Helena Br.; Nour Farozi Agus; Kahar Hakim (MultiTech Publisher, 2024)
This study examines the management of Non-Tax State Revenue from State Property Utilization at the Bengkulu State Wealth and Auction Service Office. It employs descriptive qualitative research methods, utilizing observation, interviews, and documentation for data collection. Analysis involves data collection, reduction, presentation, and conclusion drawing. The research is guided by Minister of Finance Regulation Number 155/PMK.02/2021 and Management Theory by Robbins and Coulter, and Henry Fayol. Findings reveal that in planning, the office follows PNBP targets set by the Central Office, employing strategies aligned with PMK Number 115 of 2021 to optimize State Property Utilization while adapting to regulatory changes. Implementation involves generating PNBP from rent, with determination and payment processes streamlined through coordination and application of PMK No. 115 of 2021. Accountability measures include financial reporting to KPPN and administrative reporting to KPKNL, ensuring transparency in utilization agreement decrees and payment proofs as performance indicators. Regarding supervision, KPKNL focuses on increasing awareness and oversight of State Property Utilization through wasdal regulation, addressing challenges, and conducting annual evaluations aligned with Key Performance Indicators (KPIs).